AB0722 Capillaroscopy and pulmonary arterial hypertension in systemic sclerosis: a systematic review. (12th June 2018) - Vanhaecke, A.; Smith, V.; Melsens, K.; Paolino, S.; Piette, Y.; Sulli, A.; Trombetta, A.C.; De Keyser, F.; Vandecasteele, E.; Cutolo, M.; ,
Abstract : Background: At this very moment, no systematic review evaluating the role of nailfold videocapillaroscopy (NVC), with standardised definitions, in pulmonary arterial hypertension (PAH) has been published. Objectives: To systematically identify and review all available literature evaluating the role of capillaroscopy in PAH in SSc, according to the definitions of the EULAR study group on microcirculation in Rheumatic diseases. Methods: A systematic literature search was performed in Pubmed, EMBASE and Web of Science. All retrieved articles were screened on title, abstract and full-text level. Reference lists and google scholar were additionally searched. Original research papers that documented an association between NVC and PAH (confirmed on right heart catheterization [RHC]) in SSc were included. Subsequently, NVC parameters were subdivided in quantitative (density, dimension, morphology and haemorrhages), semi-quantitative (NVC score) and qualitative assessment (presence of scleroderma pattern, severity of scleroderma pattern and worsening of scleroderma pattern) according to the definitions of the EULAR study group on microcirculation in Rheumatic diseases. Results: The systematic search identified 215 unique search results, of which 171 references were withheld after title screening. Abstract screening resulted in 51 references, only 19 were eligible for full-text review. Finally, 9 references were included in the final analysis after full-text screening (n=7) and bibliographic and google scholar search (n=2) (see table 1). Regarding cross-sectional studies, density has been evaluated in 5 studies, with no unequivocal results for mean density; avascular score has been unequivocally associated with PAH. Dimension has been evaluated in 4 studies, with no unequivocal results. Morphology has been evaluated in 1 study and has been unequivocally associated with PAH. Haemorrhages and scleroderma pattern has been evaluated in 1 and 2 studies respectively, with no association. Severity of scleroderma pattern has been evaluated in 3 studies and has been unequivocally associated with PAH. Regarding longitudinal studies, density (i.e. capillary loss) has been evaluated in 2 studies and has been unequivocally associated with incident PAH. Dimension and haemorrhages have been evaluated in 1 study both, with no association. Morphology has been evaluated in 2 studies, with no unequivocal results. Worsening of scleroderma pattern has been evaluated in 2 studies and has been unequivocally associated with incident PAH. Conclusions: This systematic literature review, on behalf of the EULAR study group on microcirculation in Rheumatic diseases, is the first to investigate unequivocal associations between (incident) PAH and capillaroscopic alterations in a standardised way. Unequivocal associations were found in cross-sectional studies between avascular score, morphology, NVC score and severity of scleroderma pattern and PAH and in longitudinal studies between capillary loss and worsening of scleroderma pattern and incident PAH. Disclosure of Interest: None declared